Prison Commitment in the Implementation of the Scabies Management Program in Class II A Prison Rantauprapat - Ida Rizkia; Zulfendri; Taufik Ashar (Britain International for Academic Research (BIAR) Publisher, 2020)
Scabies is a contagious skin infection caused by infestation and sensitivity to Sarcoptes scabiei varietahominis which is included in the Arachnida class. Data obtained from the Class II-A Prison clinic that the disease that is often experienced by prisoners is a skin disease such as scabies. The policy for scabies prevention and prevention in Class II-A Prison Rantauprapat has been pursued in 2017, but these efforts have not yet yielded encouraging results, because the number of scabies sufferers continues to increase each month. The purpose of this study is to see the commitment of prisons in the implementation of scabies program in Class II-A Prison in Rantauparapat. This qualitative research method uses case studies with in-depth interviews and includes various sources of information. There were five informants in this study, namely 1 Head of Class II-A Prison Rantauprapat, 1 prison Doctor, 1 prison Nurse, 2 prison. The results showed that the commitment of the prison party was quite low so that the implementation of the scabies program in Class II-A Prison Rantau Parapat was not going well.